Kebijakan Penanganan Pengungsi dari Luar Negeri di Kota Makassar - Sapada, Andi Tenri; Hamzah, Yuli Adha; Darmawansya TL, Andi (Amsir Law Journal, 2023)
Refugees and asylum seekers often hold demonstrations, making demands, to be immediately sent to the resettlement country. Several demonstrations by refugees and asylum seekers indicate that there are problems in handling them. How is the handling of refugees and asylum seekers from abroad in Makassar City, and are there any things that affect the handling of refugees and asylum seekers from abroad in Makassar City? The research method used is juridical-empirical, namely research that focuses on field research. The number of refugees in the Makassar City area was recorded in 2022 as many as 1,369 people and all of them have been assigned the status of refugees by UNHCR. Placed in 22 community houses facilitated by the International Organization for Migration (IOM). Implementation of Presidential Regulation Number 125 of 2016 concerning Handling of Refugees from Abroad in Makassar City, including aspects of finding, placing, securing, and monitoring immigration and the factors that influence its implementation. Throughout 2022 there were no findings of refugees in an emergency situation in the Makassar City area, while the existence of refugees and asylum seekers who entered Makassar City was transferred from shelters in other areas in Indonesia. The shelter for refugees and asylum seekers is the responsibility of the City Government of Makassar. In its implementation, the City Government of Makassar in cooperation with IOM has fulfilled the specified requirements. Influential factors are social and cultural factors that are prone to causing problems between refugees and local communities. In terms of security, it is still not implemented optimally. The implementation of immigration control, especially for refugees outside shelters, has not been carried out optimally. ___ Referensi Buku dengan penulis: Alimuddin, A. F. F. (2020). Efektivitas Penegakan Hukum terhadap Penyalahgunaan Izin Keimigrasian oleh Pencari Suaka di Kota Makassar. Makassar: Universitas Bosowa. Sultoni, Y. (2014). Alasan Indonesia Belum Meratifikasi Konvensi 1951 Tentang Pengungsi dan Perlindungan Hukum Bagi Pengungsi di Indonesia. Malang: Brawijaya University. Vita Indah, P. (2021). Kebijakan Politik Luar Negeri Indonesia terhadap Pengungsi Asing dan Pencari Suaka Pada Era Reformasi Perspektif Siyāsah Dauliyah. Purwekerto: IAIN Purwokerto. Artikel jurnal: Darussalam, A., Bachtiar, F. R., dan Zulfikar, A. (2021). Tinjauan Sikap dan Kebijakan Negara-Negara Terkait Pengungsi Timur Tengah: Peran Strategis Negara-Negara Mayoritas Muslim dalam Perspektif Islam. Gorontalo Journal of Government and Political Studies, 4(1), 146-166. Fajriana, N. (2018). Teleconference Dalam Pemeriksaan Perkara Pidana di Pengadilan. Badamai Law Journal, 3(1), 60-79. Johan, E. (2013). Kebijakan Indonesia terhadap Imigran Ilegal dan Hubungannya dengan Kedaulatan Negara. Yuridika, 28(1), 1-12. Khairiah, N., Rahmi, A., dan Martinelli, I. (2021). Management of Overseas Refugees in North Sumatra in the Perspective of Human Security. Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 4(4), 12077-12089. Mardizan, L. P., dan Syamsir, S. (2019). Pengawasan Penerbitan Paspor dalam Rangka Pencegahan TKI Nonprosedural di Kantor Imigrasi Kelas I Padang. Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 1(1), 97-115. Primawardani, Y., dan Kurniawan, A. R. (2018). Penanganan Pengungsi dari Luar Negeri oleh Petugas Rumah Detensi Imigrasi di Provinsi Sulawesi Selatan. Jurnal Ilmiah Kebijakan Hukum, 12(2), 179-197. Rompas, K., Liando, D. M., dan Waworundeng, W. (2021). Implementasi Kebijakan Pengawasan Orang Asing di Provinsi Sulawesi Utara. Pengelolaan Sumberdaya Pembangunan, 1(1), 1-9. Syahrin, M. A., dan Utomo, Y. S. (2019). Implementasi Penegakan Hukum Pencari Suaka dan Pengungsi di Indonesia Setelah Diberlakukannya Peraturan Presiden Nomor 125 Tahun 2016 tentang Penanganan Pengungsi dari Luar Negeri. Jurnal Ilmiah Kajian Keimigrasian, 2(2), 83-96. Syahrin, M. A., dan Saputra, S. (2019). Tindakan Hukum terhadap Orang Asing Mantan Narapidana yang Memiliki Kartu Pengungsi UNHCR dalam Perspektif Keimigrasian. Jurnal Ilmiah Kebijakan Hukum, 13(2), 139-164. Utomo, H., Yusnaldi, Y., dan Puspita, A. S. (2018). Upaya Pemerintah Menangani Irregular Migrant Dalam Perspektif Keamanan Maritim di Provinsi Daerah Istimewa Yogyakarta. Keamanan Maritim, 4(2), 87-109.